Re-humanisation and future: The crisis of modern philosophy and the idea of re-humanisation as a project for a future philosophy of life - Cañas Fernández, José Luis (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
This article attempts to give an answer to the fundamental question of what personal life means from the perspective of re-humanisation. In order to do that, we will review the two opposing concepts about the human being that have underpinned modern philosophy since its inception: a transcendental anthropological vision of life represented by the philosophy of Sören Kierkegaard, vs an imminent anthropological vision of life associated with Friedrich Nietzsche. This analysis will allow us to articulate a philosophy of re-humanisation linked to a Science of the Person that looks to the future as a hopeful task.